2017
DOI: 10.1037/drm0000058
|View full text |Cite
|
Sign up to set email alerts
|

Sex dreams in married women: Prevalence, frequency, content, and drives.

Abstract: Although sex dreams (SD) are of common occurrence, studies dealing with them are still restricted. SD had been reported as accompanying nocturnal orgasms in women and they were reported usually as a reflection of their actual experience. This cross-sectional descriptive study aimed to provide information about SD prevalence, frequency, content, and drives in a group of Egyptian married women. Overall, 211 married women answered a self-report questionnaire including 23 items covering the epidemiology of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
2
9
1
Order By: Relevance
“…Among the findings put forth by the handful of studies on correlates of sexual dreams, the observations that the occurrence of such dreams often parallels the frequency of sexual intercourse (Younis et al, 2017), of orgasmic experience (King et al, 2009), and time spent thinking about sexually related fantasies (King et al, 2009;Schredl et al, 2009) are consistent with the continuity hypothesis of dreaming. In addition, one study of 98 female undergraduates found that dreams about infidelity were associated with having had an unfaithful partner and with higher daytime levels of romantic jealousy.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Among the findings put forth by the handful of studies on correlates of sexual dreams, the observations that the occurrence of such dreams often parallels the frequency of sexual intercourse (Younis et al, 2017), of orgasmic experience (King et al, 2009), and time spent thinking about sexually related fantasies (King et al, 2009;Schredl et al, 2009) are consistent with the continuity hypothesis of dreaming. In addition, one study of 98 female undergraduates found that dreams about infidelity were associated with having had an unfaithful partner and with higher daytime levels of romantic jealousy.…”
mentioning
confidence: 73%
“…However, the same study also found that sexual dreams involving the current partner or sexual targets other than one's current partner were unrelated to dreamer's level of relationship satisfaction (Clarke et al, 2010). Similarly, a study of 211 married Egyptian women found that sexual dreams were unrelated to overall sexual satisfaction but were related to the frequency of sexual intercourse with the partner (Younis et al, 2017). Whether these findings hold true for men or in more diverse, nonstudent samples of women in committed relationships has yet to be investigated.…”
mentioning
confidence: 99%
“…More than 70% of people have experienced sexual dreams in general population [14] There is a specific concern about sexual dreams in psychiatric patients as they have different features, for example, in schizophrenic patients, it was found that in their dreams there was less sexual contents, but more aggression and sadism [15] Sexual dreams may reflect the waking-day life, ethical concerns, and social problems. The related experience includes different people and settings, and brings various feelings, but there is no systematic measure available to date [16] In a study conducted by [17], it was found that occurrence of sexual dreams was more common in women aged 20-29 years, in those having a university degree and in housewives. Its frequency was proportional to coital frequency and the frequency of orgasm.…”
Section: Resultsmentioning
confidence: 99%
“…The tool used in this study was a questionnaire designed according to [17] Other questions were added to suit the purpose of study. This questionnaire was written in English and translated into Arabic.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, sexual pleasure or emotional satisfaction during sexual dreams was frequently reported by men [ 13 ] and women. [ 40 ] There are also some cultural-specific differences on sexuality, for instance, East-Asian people tended to have higher sexual guilt than their Western counterparts. [ 41 , 42 ] Therefore, our Chinese dreamers might have averse feelings during waking time due to the conservative sex values despite that they might have pleasant sexual dreams.…”
Section: Discussionmentioning
confidence: 99%